Landslide Disaster Risk for Small and Medium Agricultural Enterprises (SMAEs) - Ngadisih; Bambang Purwantana; Devi Yuni Susanti; Ismi N. Puspitaningrum; Guruh Samodra; Peter Strauss; Sigit Supadmo Arif; Murtiningrum; Sri Rahayoe; Joko Nugroho W.K.; Lilik Sutiarso; Nursigit Bintoro; et al. (Environment and Natural Resources Journal)
Small and Medium Agricultural Enterprises (SMAEs) are crucial for economic development in many developing countries, particularly in rural areas. Following a disaster, SMAEs experience the most profound impacts on their capital, logistics, workforce, and marketing operations. This study examines the impact of landslides on SMAEs in Selopamioro village, Bantul Regency of Special Region Yogyakarta. The study focused on the economic sensitivity of SMAEs and assessed their spatial distribution and classifications using drone aerial imagery and a village landslide database from 2010 to 2024. A total of 120 SMAEs were identified and classified by type in accordance with Indonesian laws. A representative sample of 60 SMAEs was validated using the Slovin formula. The study employed a hybrid survey methodology, combining interviews with village and hamlet leaders and on-site surveys using standardized questionnaires. The results showed that SMAEs in all hamlets of Selopamioro village have relatively low sensitivity, indicating that recent landslides have had limited effects on their sustainability. The village’s disaster response capacity was moderate, but the study identified deficiencies in planning for potential future landslides. This study provides valuable insights for SMAEs and local governments regarding proactive risk mitigation strategies.